The Influence of Self-Control and Social Status on Self-Deception - Ren, Mengmeng; Zhong, Bowei; Fan, Wei; Dai, Hongmei; Yang, Bo; Zhang, Wenjie; Yin, Zongxiang; Liu, Juan; Li, Jin; Zhan, Youlong (Frontiers in Psychology, 2018)
The purpose of this study was to explore the effects of self-control and social status on self-deception. The present study adopted a forward-looking paradigm to investigate how self-control and social status influence self-deception. In Experiment 1, participants were asked to complete 10 questions, after they predicted and completed 40 questions (commonsense judgment materials) either with or without answer hints. The results indicated that the participants had higher predicted scores under conditions with answer hints compared with conditions without answer hints and that the predicted scores were much higher than the actual scores under conditions with answer hints. In Experiment 2, individuals with different self-control traits were chosen to perform the operation and induction of the perception of social status and then complete tests such as Experiment 1. The results showed that differences in the predicted scores between conditions with answer hints and those without answer hints were observed to be greater in individuals with low self-control traits than in individuals with higher self-control traits; however, such differences between individuals with higher and low self-control traits were only observed in conditions with low social status perception, not in the conditions with high social status perception. The findings indicated that compared with individuals with high self-control, low self-control individuals tended to produce more self-deception. In addition, high social status in the individuals’ perception could restrain the influence of low self-control on self-deception, while low social status in the individuals’ perception could increase the self-control's influence on self-deception.